2023
DOI: 10.1038/s41598-023-41713-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world analysis of survival benefit of surgery and adjuvant therapy in elderly patients with colorectal cancer

Lei Zhang,
Qixin Li,
Chenhao Hu
et al.

Abstract: Treatment guidelines for colorectal cancer (CRC) in elderly patients remain unclear. This study aimed to investigate whether elderly patients (≥ 70 years) with CRC benefit from surgery and adjuvant therapy. A total of 90,347 eligible CRC patients older than 70 years were collected from the Surveillance, Epidemiology, and End Results (SEER) database and divided into a surgery group and a no-surgery group. After being matched by propensity score matching at a 1:1 ratio, 23,930 patients were included in our analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Patients with localized disease aged 75–79 had an OS exceeding 70% and those aged 80–84 had an OS of over 50%, whereas the respective DSS is remarkably better (over 90% and 80%). A similar pattern among elderly CRC patients was noted in a recent study based on the SEER database [ 12 ]. That study demonstrated that elderly patients undergoing surgery usually have a better OS and DSS than those receiving palliative treatment alone.…”
Section: Discussionsupporting
confidence: 85%
“…Patients with localized disease aged 75–79 had an OS exceeding 70% and those aged 80–84 had an OS of over 50%, whereas the respective DSS is remarkably better (over 90% and 80%). A similar pattern among elderly CRC patients was noted in a recent study based on the SEER database [ 12 ]. That study demonstrated that elderly patients undergoing surgery usually have a better OS and DSS than those receiving palliative treatment alone.…”
Section: Discussionsupporting
confidence: 85%